Surgical site infection in immediate breast reconstruction: Does chemotherapy timing make a difference?. Issue 7 (25th March 2018) - Chattha, Anmol S.; Cohen, Justin B.; Bucknor, Alexandra; Chen, Austin D.; Tobias, Adam M.; Lee, Bernard T.; Lin, Samuel J.
Abstract : Background and Objectives: We aim to analyze the impact of chemotherapy timing on surgical site infections (SSI) after immediate breast reconstruction (IBR). Methods: A retrospective review of patients undergoing IBR between 2010 and 2015 was performed. Patients were divided into four groups: those with neoadjuvant chemotherapy only, adjuvant chemotherapy only, both adjuvant and neoadjuvant, and those with no chemotherapy. Outcomes of interest included SSI and timing of post‐operative SSI. Results: A total of 949 reconstructions were performed over the study period. Subgroup breakdown was as follows: A total of 56 (5.9%) neoadjuvant only, 173 (18.2%) adjuvant only, 18 (1.9%) both, and 702 (74.0%) none. Overall infection rates were 10.7%, 10.4%, 22.2%, and 6.1% in the four groups, respectively ( P = 0.015). On multivariate analysis, no significant differences were observed when comparing presence or absence of chemotherapy in the overall reconstruction cohort or when subgrouped by reconstruction modality‐autologous or alloplastic. There were no significant differences in time from neoadjuvant chemotherapy to surgery date noted between patients who developed a post‐operative SSI and those who did not (4.40 ± 1.58 vs 4.72 ± 1.39 weeks; P = 0.517). Conclusion: Chemotherapy timing did not increase the odds of surgical site infections in patients undergoing immediate breast reconstruction.